Hermansky-Pudlak Syndrome and Lung Disease: Pathogenesis and Therapeutics - Velázquez-Díaz, Pamela; Nakajima, Erika; Sorkhdini, Parand; Hernandez-Gutierrez, Ashley; Eberle, Adam; Yang, Dongqin; Zhou, Yang (Frontiers in Pharmacology, 2021)
Hermansky-Pudlak Syndrome (HPS) is a rare, genetic, multisystem disorder characterized by oculocutaneous albinism (OCA), bleeding diathesis, immunodeficiency, granulomatous colitis, and pulmonary fibrosis. HPS pulmonary fibrosis (HPS-PF) occurs in 100% of patients with subtype HPS-1 and has a similar presentation to idiopathic pulmonary fibrosis. Upon onset, individuals with HPS-PF have approximately 3 years before experiencing signs of respiratory failure and eventual death. This review aims to summarize current research on HPS along with its associated pulmonary fibrosis and its implications for the development of novel treatments. We will discuss the genetic basis of the disease, its epidemiology, and current therapeutic and clinical management strategies. We continue to review the cellular processes leading to the development of HPS-PF in alveolar epithelial cells, lymphocytes, mast cells, and fibrocytes, along with the molecular mechanisms that contribute to its pathogenesis and may be targeted in the treatment of HPS-PF. Finally, we will discuss emerging new cellular and molecular approaches for studying HPS, including lentiviral-mediated gene transfer, induced pluripotent stem cells (iPSCs), organoid and 3D-modelling, and CRISPR/Cas9-based gene editing approaches.